2020
DOI: 10.1088/1755-1315/537/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Study of aerosol content based on spectrophotometric observations: A comparison with long-term extinction profile from photometric observations

Abstract: Spectroscopic observations of standard stars (spectrophotometric) have been carried out at Bosscha Observatory ITB (latitude= 6°49′28″ S, longitude= 107°36′56″ E, altitude=1310 m) using the Celestron C-11 reflector (D=11 inches, F/10.0), equipped with NEO R-1000 spectrograph (Resolution of 1000), and ST-8XME CCD camera to deduce total atmospheric extinction curve. Spectrograms were reduced with the long-slit task in the Image Reduction and Analysis Facility (IRAF). The total extinction curve obtained from obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Here 𝑀 𝑧,band is the apparent magnitude measured inside atmosphere, 𝑀 0,band is the extra-atmospheric magnitude, and 𝐾 band is atmospheric extinction coefficient. 𝐹 (𝑧) is airmass which is adopted as follows [32]:…”
Section: Atmospheric Extinction Coefficientmentioning
confidence: 99%
“…Here 𝑀 𝑧,band is the apparent magnitude measured inside atmosphere, 𝑀 0,band is the extra-atmospheric magnitude, and 𝐾 band is atmospheric extinction coefficient. 𝐹 (𝑧) is airmass which is adopted as follows [32]:…”
Section: Atmospheric Extinction Coefficientmentioning
confidence: 99%
“…Based on the moonlit sky brightness modelling,Yao et al (2013) derived 𝑘 = 0.23 for Xinglong Station China. At Bosscha Observatory,Malasan et al (2020) reported the extinction coefficient between 0.30 and 0.88 based on the spectroscopic observation (4200 − 7000 Å) in 2019. That quoted value is more than double the coefficient derived for the same site in 1993.…”
mentioning
confidence: 99%